Effects of carbohydrate-protein ingestion post-resistance training in male rugby players - Coyle, C. J.; Donne, B.; Mahony, N. J. (International Journal of Exercise Science, 2012)
Evidence suggests that carbohydrate-protein (CHO-PRO) drinks post-exercise are an advantageous nutritional recovery intervention. Resistance trained (n = 14, mean ± SD; age 19 ± 1 yr, mass 95 ± 9 kg, % fat 17 ± 4 % and BMI 28.5 ± 1.8 kg.m-2) male rugby players participated in a study investigating effects of carbohydrate (CHO) and CHO-PRO drinks on subsequent resistance exercise performance. Following an initial resistance training (RT) protocol consisting of 8 circuits of 5 discrete exercises at 10 repetition maximum (RM), participants received 10 mL.kg-1 BM of randomised sports drink (LCHO, HCHO and CHO-PRO) on completion of the RT protocol and at 120 min into a 240 min recovery period. Post-recovery, participants completed a test to failure (TTF) protocol performing as many circuits of the same exercises at 10-RM to failure. Individual exercise cumulative load (.W) lifted and total work capacity (TWC) for each trial was recorded. Both .W and TWC were normalised for body mass (kg.kg-1 BM). Data were analysed using repeated measures ANOVA with post-hoc Student- Neuman-Keuls pair-wise comparisons (P<0.05). Despite large intra-subject variability between trials, TWC normalised for body mass was significantly greater following CHO-PRO compared with HCHO and LCHO (188 ± 26 vs. 157 ± 21 and 150 ± 16 kg.kg-1 BM, respectively; P<0.05). The .W lifted after ingestion of HCHO and LCHO were not significantly different despite differing CHO and caloric content. The CHO-PRO induced enhancement of recovery was possibly